Teaching ESP vocabulary to students majoring in Heat and Refrigeration Engineering at Industry University of Ho Chi Minh City: difficulties and suggestions for solutions - Nguyễn, Thị Thúy Hằng (University of Languages and International Studies, 2017)
Individual fields of science technology differ mainly in their vocabulary. That is why vocabulary learning and teaching is considered to be a decisive factor in Heat and Refrigeration Engineering English study. As observation and review are carried out in (...)